Immersive Analytics Lessons from the Electronic Visualization Laboratory: a 25 Year Perspective - Marai, G.E. (IEEE Comput Graph Appl, 2019)
This article provides a 25 year-long perspective on Immersive Analytics through the lens of first-in-kind technological advancements introduced at the Electronic Visualization Laboratory, University of Illinois at Chicago, along with the challenges and lessons learned from multiple Immersive Analytics projects.